Pericarditis Diagnosis and Management Challenges - Berezin, Alexander E. (IntechOpen, 2023)
This book is not about clear cases of acute and chronic pericarditis, but about unresolved issues not covered by current clinical guidelines that frequently create unexpected difficulties in the management of the disease in routine clinical practice. Here we discuss different kinds of diagnostic management from conventional echocardiography to advanced visualization procedures, such as magnetic resonance imaging and biopsy procedures, with the aim of clearly elucidating novel approaches to establishing the presence of the disease, predicting its natural course and determining its management. Although pericarditis of unknown etiology is frequently encountered in clinical practice, specific serological markers and culture tests are not regarded as final decision tools to thoroughly establish plausible causes of the disease in patients without clear backgrounds, signs and symptoms of heart failure, and concomitant conditions. In this respect, endocardial and pericardial biopsy, combined visualization procedures, such as contrast-enhanced magnetic resonance imaging with 3D-computer tomography modeling of cardiac function, are the next steps in contemporary management. The surgical approach, along with clear descriptions of patients' enrollment and predicted outcomes, are also described in this book.